Incidence rates of malignancies and hospitalized infectious events in patients with psoriasis with or without treatment and a general population in the U.S.A.: 2005–09. (February 2014) - Kimball, A.B.; Schenfeld, J.; Accortt, N.A.; Anthony, M.S.; Rothman, K.J.; Pariser, D.
<x xml:space="preserve">Abstract</x> What's already known about this topic? Some evidence shows elevated rates of malignancies and serious infections among psoriasis patients in general but also for those on therapeutic regimens. What does this study add? This study provides evidence that the elevated rates of malignancy and serious infections found in psoriasis patients may be due to biological reasons other than specific treatment modalities.